Abdominal Sarcoidosis May Mimic Peritoneal Carcinomatosis. (8th October 2015) - Gorkem, Umit; Gungor, Tayfun; Bas, Yılmaz; Togrul, Cihan
Abstract : Sarcoidosis is a multisystem inflammatory disorder of unknown etiology. It shows a great variety of clinical presentation, organ involvement, and disease progression. Lungs and lymphoid system are the most common sites involved with a frequency of 90% and 30%, respectively. Extrapulmonary involvement of sarcoidosis is reported in 30% of patients and abdomen is the most frequent site. Furthermore, peritoneal involvement is extremely rare in sarcoidosis. The case presented here described peritoneal manifestations of sarcoidosis without involvement of lungs. A 78-year-old woman possessing signs of malignancy on blood test and abdominal magnetic resonance imaging underwent laparatomy with a suspicion of ovarian malignancy. The macroscopic interpretation during surgery was peritoneal carcinomatosis. Total abdominal hysterectomy, bilateral salpingo-oophorectomy, peritoneal biopsies, total omentectomy, and appendectomy were performed. Final histopathological result revealed the diagnosis of sarcoidosis. Clinicians must keep in mind that peritoneal sarcoidosis can mimic intra-abdominal malignancies.